Management of the Impression of Maintaining Sakinah Family Image and the Reality of Hidden Economic Violence: A Qualitative Study of the Phenomenon of Domestic Violence in Wives of Public and Informal Sector Workers - Uun Machsunah; Endah Nurhawaeny Kardiyati; Ririn Risnawati (ann4publisher@gmail.com, 2026)
Background. Domestic violence (KDRT) is often only identified as physical abuse, while economic violence (economic abuse) and verbal-psychological terror are frequently hidden, especially when driven by the pressure to maintain a prestigious family image in society. Aims. This study aims to analyze the mechanisms of economic and psychological violence experienced by wives from different socio-economic backgrounds, and how they perform